2012
DOI: 10.1590/s0100-83582012000400001
|View full text |Cite
|
Sign up to set email alerts
|

Potential of macrophyte for removing arsenic from aqueous solution

Abstract: -The potential of three aquatic macrophytes, Azoll caroliniana, Salvinia minima and Lemna gibba, was evaluated in this work aimed at selection of plants to be used in remediation of environments contaminated by arsenic (As). The experiments were carried out in a greenhouse during six days in pots containing Hoagland solution (¼ ionic strength) at As concentrations of 0.5; 2.5 and 5.0 mg L -1 . The three species showed greater As accumulation as the concentration of the metalloid in solution increased. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 44 publications
1
12
1
Order By: Relevance
“…Symptoms like these are typical of the toxicity of metals to macrophytes, some however, may be specific to each species (Guimarães et al, 2012). These authors observed in the Azolla caroliniana Willd.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Symptoms like these are typical of the toxicity of metals to macrophytes, some however, may be specific to each species (Guimarães et al, 2012). These authors observed in the Azolla caroliniana Willd.…”
Section: Discussionmentioning
confidence: 93%
“…In general, the roots of macrophytes play a key role in the accumulation of substances. For Barros and Henares (2015), this is assertive for floating aquatic weeds, which absorb most of the nutrients through this compartment, with the area and the length of the root being factors which influence the absorption of metal ions. In studies with macrophytes coming from contaminated water systems, the floating species S. auriculata and E. crassipes were highlighted by the high levels of mercury (Hg) present in their biomass, mainly in the roots (Molisani et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lemna gibba (duckweed) is an aquatic plant that has been reported to uptake large quantities of arsenic and is considered a hyperaccumulator of this element (Mkandawire et al 2004;Guimaraes et al 2012). Almost all studies that correlate L. gibba with arsenic are based on the capacity of this plant to accumulate metals and mineral nutrients (Mkandawire & Dudel 2005;Mkandawire et al 2006;Sasmaz & Obek 2009;Guimaraes et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Almost all studies that correlate L. gibba with arsenic are based on the capacity of this plant to accumulate metals and mineral nutrients (Mkandawire & Dudel 2005;Mkandawire et al 2006;Sasmaz & Obek 2009;Guimaraes et al 2012). Based on the fact that the comprehension of the physiological aspects involved in arsenic tolerance mechanisms is essential to the application of phytoremediation, and considering that oxidative stress is one of the main causes of damage to plants caused by heavy metals, the aim of this work was to study the effects of arsenic on the enzymatic and nonenzymatic antioxidant mechanisms that are ordinarily involved in defense mechanisms.…”
Section: Introductionmentioning
confidence: 99%